(untitled) (Journal of the College of Basic Education, 2022)
PEG/Zn(ext)2 with ( x= 0, 0.2, 0.4, 0.6) thin films have been prepared by spin coating method .The influence of zinc complex on PEG/Zn(ext)2 thin films have been investigated by the X-ray diffraction (XRD), Atomic Force Microscope (AFM) and DC electrical conductivity. , the FT-IR test were necessary to identify the functional groups in the prepared samples, As well as to detect the doped that added to the samples. The study of electrical conductivity show the pure sample .The DC electrical conductivity studies show that conductivity values of the films increase from (1.33x10-9) S/cm to(3.42x10-7)S/cm as the Zn(ext)2 concentration increases.